Kabsahan Kesepakatan Lisan dalam Pembagian Warisan: Studi Kasus Putusan Nomor 18/PDT.G/2024/PN.MET - Chyntia Felisiane; Pieter E. Latumeten (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Inheritance is a legal event involving the transfer of assets from the deceased (the heir) to their successors, who may be related by blood, marriage, or by will. The right to control a parcel of land is generally one of the main interests of heirs. When there is more than one heir, a legal basis is required to formalize the distribution of land rights, which is done through a Deed of Joint Rights Distribution (Akta Pembagian Hak Bersama or APHB) prepared by a Land Deed Official (Pejabat Pembuat Akta Tanah or PPAT). This study employs a normative juridical method by examining various theories, concepts, and statutory regulations relevant to the topic, using legal norms as the primary reference. In this research, agreements that are mandated by law must be executed accordingly; failure to do so renders such agreements invalid, null and void by law, and considered as never having been formed. Consequently, the plaintiffs lack a legal basis to request a court order authorizing them to sign the APHB on behalf of the defendants. As a result, the legal status of land ownership cannot be officially transferred to the respective heirs in accordance with the planned distribution. The most significant implication for the parties involved, particularly the plaintiffs, is that the legal status of the inherited land remains unchanged due to the rejection of their claim. The findings of this study indicate that verbal agreements do not have binding legal force for all heirs, and that the legal implication of the court's decision is that the inheritance distribution cannot proceed in the absence of a court order mandating the partition of the land certificate in accordance with the plaintiffs' demands.